2016
DOI: 10.18296/am.0019
|View full text |Cite
|
Sign up to set email alerts
|

How teachers of Years 4–8 students analyse, interpret and use information from the Progressive Achievement Test: Mathematics

Abstract: Assessment can be powerful when teachers are able to analyse, interpret and use information in ways that enhance their teaching and programmes, and students' learning. A qualitative approach was used to investigate how teachers of Years 4-8 students analyse, interpret and use information gained from administration of the Progressive Achievement Test: Mathematics (PAT: Mathematics) assessment tool. Six teachers from two schools in a rural district, south of Auckland, participated in the study. Teachers at one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Pierce and Chick (2011), in their study of Australian Mathematics and English teachers' intentions to engage with externally produced statistical data, found that most teachers considered the data could be used to identify weak students and some teachers (mostly mathematics teachers) thought that they could help to identify curriculum topics that needed attention. In a teacher study in New Zealand, Caldwell and Hawe (2016) concluded that a systematic approach to standardized data was needed for students, teachers, schools and other stakeholders to gain full benefit from the data. A challenge in our research was to know more about the processes and supports needed for teachers to learn with and through data and to exploit any opportunities this might offer to create new and productive opportunities for improving student learning and achievement.…”
Section: The Use Of Standardized Data For Pedagogical Decision-making and Instructional Actionmentioning
confidence: 99%
“…Pierce and Chick (2011), in their study of Australian Mathematics and English teachers' intentions to engage with externally produced statistical data, found that most teachers considered the data could be used to identify weak students and some teachers (mostly mathematics teachers) thought that they could help to identify curriculum topics that needed attention. In a teacher study in New Zealand, Caldwell and Hawe (2016) concluded that a systematic approach to standardized data was needed for students, teachers, schools and other stakeholders to gain full benefit from the data. A challenge in our research was to know more about the processes and supports needed for teachers to learn with and through data and to exploit any opportunities this might offer to create new and productive opportunities for improving student learning and achievement.…”
Section: The Use Of Standardized Data For Pedagogical Decision-making and Instructional Actionmentioning
confidence: 99%